1999
DOI: 10.1038/sj.ijo.0801061
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child relationship of physical activity patterns and obesity

Abstract: OBJECTIVE: To study differences in physical activity between normal-weight and obese children, as well as parent ± child associations of obesity and physical activity. DESIGN: Cross-sectional study. SUBJECTS: 129 obese children (67 girls and 62 boys), 142 normal-weight controls (81 boys and 61 girls), and mothers (n 245) and fathers (n 222) of the children. METHODS: Physical activity was assessed by a 3-day physical activity record (children and parents), by a questionnaire (children), and by one question on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
167
2
8

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(191 citation statements)
references
References 34 publications
(33 reference statements)
14
167
2
8
Order By: Relevance
“…Lifestyle factors associated with childhood obesity development in other studies, such as television watching 14 and inactivity, 15,42 were not shown to be important risk factors in our study. Hong Kong children have been noted in other studies to be very inactive, and this was supported by our data which showed that 76% of subjects did no exercise during schooldays and 24% did not have regular exercise on both schooldays and holidays.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Lifestyle factors associated with childhood obesity development in other studies, such as television watching 14 and inactivity, 15,42 were not shown to be important risk factors in our study. Hong Kong children have been noted in other studies to be very inactive, and this was supported by our data which showed that 76% of subjects did no exercise during schooldays and 24% did not have regular exercise on both schooldays and holidays.…”
Section: Discussionmentioning
confidence: 40%
“…It is generally agreed that obesity is caused by both genetic 9 and environmental factors. 10 Some well-known factors such as parental obesity, 11 excessive energy intake, 12,13 inactivity 14,15 and some new concerns such as early infant nutrition, [16][17][18] maternal smoking 19 and sleep duration 20 have been highlighted. However, in contrast to the genetic determinants, findings related to environmental risk factors, such as social factors, 21 dietary factors and physical activity, 22 have tended to be inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance to our study, von Kries et al identified obesity of the parents, a high birth weight and a low SES as significant risk factors; additionally, TV watching and smoking during pregnancy influenced the risk of childhood overweight. In a multivariate analysis Strauss and Knight, 27 Fogelholm et al, 28 Maffeis et al, 29 as well as Hediger et al, 30 also identified parental overweight and obesity as the strongest determinants of childhood overweight.…”
Section: Discussionmentioning
confidence: 99%
“…10 The characteristics of the environment that influence physical activity and body size may be similar for young children and their parents. A child's body size is strongly correlated with his or her parents' body size, 11,12 and parental weight change predicts childhood weight change. 13,14 Very young children depend on an adult to take them out and bring them home.…”
mentioning
confidence: 99%